The determinants of success in university entrance - Botelho, Anabela (2001)
This paper proposes that high school graduates applying to higher education institutions do not have equal chances of succeeding. Therefore, admission outcomes must be taken into account by researchers and policy makers analysing college-going behaviour and the equity and efficiency of higher education systems.